Structural steel plate damage detection using non destructive testing, frame energy based statistical features and artificial neural networks - Paulraj, Murugesa Pandiyan, Dr. (Malaysian Technical Universities Network (MTUN), 2013)
Malaysian Technical Universities Conference on Engineering and Technology (MUCET) 2012 organised by technical universities under the Malaysian Technical Universities Network (MTUN), 20th - 21st November 2012 at Hotel Seri Malaysia, Kangar, Perlis.